AID-I GLR project: perspective from USAID chief scientist - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
Dr. Rob Bertram, Chief Scientist at USAID's Bureau for Resilience, Environment, and Food Security, commends the AID-I GLR Project for its impactful interventions in Burundi, DRC, and Rwanda. He highlights the project's key achievements in advancing food security and strengthening seed systems in the region.